EFFECT OF IMPROVING THE LIVING CONDITIONS OF EGG LAYING CHICKENS ON PRODUCTIVITY AND SOME PHYSIOLOGICAL INDICATORS - Shokhzod Shermatovich Khudayberdiyev; Yunus Samandarovich Ruziev (Galaxy International Interdisciplinary Research Journal, 2021)
Enrichment of poultry habitats in poultry farms using environmental enrichment methods is more effective than empty cage systems, because for such kind of poultries raised outdoors or in a free-range home becomes this opportunity.In our researches, the production of eggs and the ratio of heterophilus to lymphocytes were improved by enriching the cages of egg-oriented poultry with perch structure and sand.